Effectiveness of Positive Couple Therapy on Marital Intimacy and Relational Resilience in Couples Referring to Counseling Centers in Bushehr City - Mohannaei, Setareh; Mousavi Shourgoli, Seyedeh Sahar (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to determine the effectiveness of positive couple therapy on marital intimacy and relational resilience among couples referring to counseling centers in Bushehr City. Methodology: This quasi-experimental study employed a pretest–posttest design with a control group. The statistical population consisted of couples who referred to counseling centers in Bushehr City. A total of 30 participants were selected through voluntary sampling and randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received eight sessions of positive couple therapy based on the model of Seligman and Csikszentmihalyi, while the control group received no intervention during the study period. Data were collected using the Thompson and Walker Marital Intimacy Questionnaire and the Sikby et al. Relational Resilience Questionnaire. Descriptive statistics and analysis of covariance (ANCOVA) were used to analyze the data while controlling for pretest scores. Findings: After controlling for pretest scores, ANCOVA results revealed a statistically significant effect of positive couple therapy on marital intimacy, F(1, 27) = 44.63, p < .001, η² = .62, and on relational resilience, F(1, 27) = 54.04, p < .001, η² = .67, indicating large effect sizes for both outcome variables. Conclusion: Positive couple therapy significantly enhanced marital intimacy and relational resilience, suggesting that this intervention is a highly effective therapeutic approach for improving the emotional and adaptive functioning of couples.